Liberalising Southeast Asian democracies: Will globalization help? - Stuart Mackenzie. (2008)
This paper discusses how the forces of globalization will influence the development of liberal democracy in Southeast Asia in a post Asian Financial Crisis environment. It considers the characteristics of globalization and the circumstances of Southeast Asia which have made the region both a major benefactor of, and also vulnerable to, the forces of globalization. The paper finds that the impact of the economic forces will have a liberalising effect, but that the critical development of institutions and civil society will be less directly influenced and could possibly be forestalled by authoritarian regimes. Globalization has served to highlight differences in culture and ethnic inequality in Southeast Asia, the consequence of which may be to lessen the immediate prospect of liberalisation. This paper concludes that whilst there are many obstacles to liberal democratisation in Southeast Asia, the forces of globalization will over time encourage more liberal forms of governance in the region.